The Structural Biology of Septins and Their Filaments: An Update - Cavini, Italo A.; Leonardo, Diego A.; Rosa, Higor V. D.; Castro, Danielle K. S. V.; D’Muniz Pereira, Humberto; Valadares, Napoleão F.; Araujo, Ana P. U.; Garratt, Richard C. (Frontiers in Cell and Developmental Biology, 2021)
In order to fully understand any complex biochemical system from a mechanistic point of view, it is necessary to have access to the three-dimensional structures of the molecular components involved. Septins and their oligomers, filaments and higher-order complexes are no exception. Indeed, the spontaneous recruitment of different septin monomers to specific positions along a filament represents a fascinating example of subtle molecular recognition. Over the last few years, the amount of structural information available about these important cytoskeletal proteins has increased dramatically. This has allowed for a more detailed description of their individual domains and the different interfaces formed between them, which are the basis for stabilizing higher-order structures such as hexamers, octamers and fully formed filaments. The flexibility of these structures and the plasticity of the individual interfaces have also begun to be understood. Furthermore, recently, light has been shed on how filaments may bundle into higher-order structures by the formation of antiparallel coiled coils involving the C-terminal domains. Nevertheless, even with these advances, there is still some way to go before we fully understand how the structure and dynamics of septin assemblies are related to their physiological roles, including their interactions with biological membranes and other cytoskeletal components. In this review, we aim to bring together the various strands of structural evidence currently available into a more coherent picture. Although it would be an exaggeration to say that this is complete, recent progress seems to suggest that headway is being made in that direction.